Perancangan Aplikasi Kumpulan Novel Dengan Menerapkan Algoritma Fibonacci Code - Intan Maharani; Muhammad Syahrizal; Kurnia Ulfa (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Text file sizes are sometimes relatively large where the better the quality of the resulting text files, the larger the file size needed to store the text files. With a very large text file size, when carrying out the transfer process the transfer process may fail because the media storage space exceeds the limit. The solution to this problem is how the text file can be compressed in order to speed up the transfer and storage of text files. Compression of text files is done by reducing the size of the text file by reducing the bits in the text file, but not eliminating the information data in it. By compressing, large data will be reduced in size so as to save storage space. In this study, the algorithm used is the Fibonacci code, by using this algorithm, the compression results of the values have different results for each value, and the compression results will be beneficial in sending, and moving text files will be easier.